Effect of Axial Pressure on Lime-Treated Expansive Soil Subjected to Wetting and Drying Cycles - Chuxuan Tang; Zheng Lu; Hailin Yao (Advances in Civil Engineering)
The impact of seasonal moisture variation on subgrade soil, including lime-treated expansive soil, has been investigated in many studies. However, when performing wetting and drying cycles, the effect of stress, which decides the behavior and mechanical properties of soil, is usually ignored. In this paper, the effect of axial surcharge pressure on the deformation and resilient modulus of lime-treated expansive soil subjected to wetting and drying cycles was investigated. A self-made apparatus was chosen to apply axial surcharge pressure and precisely control the variation of moisture content. The lime-treated specimens were placed in the self-made apparatus and then subjected to wetting and drying cycles under three different surcharge pressures. The results show that the axial surcharge pressure has a significant influence on the development of axial strain and resilient modulus. In particular, larger surcharge pressure induces accumulate irreversible shrinkage, whereas lower surcharge pressure tends to lead to irreversible swelling. On the contrary, the larger surcharge pressure leads to higher resilient modulus of the tested specimen after wetting and drying cycles.